1997
DOI: 10.4141/p96-014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hull removal and pearling on Fusarium species and trichothecenes in hulless barley

Abstract: . 1997. The effect of hull removal and pearling on Fusarium species and trichothecenes in hulless barley. Can. J. Plant Sci. 77: 161-166. Fourteen samples consisting of three cultivars of hulless barley (Hordeum vulgare L.), grown commercially in southern Manitoba in 1994, were examined for levels of Fusarium species and seven fusarium trichothecene mycotoxins: deoxynivalenol (DON), diacetoxyscirpenol, 15-acetyldeoxynivalenol (15ADON), fusarenone-X, HT-2 toxin, neosolaniol and T-2 toxin. Four fractions from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
10
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 11 publications
(12 reference statements)
6
10
0
1
Order By: Relevance
“…Regarding the correlation of FHB parameters with the hull trait, the results were not consistent in literature. According to Clear et al (1997), over 50% of DON initially present on barley grain could be removed during the dehulling process, which was in agreement with the results of Zhou et al (1991) and Legzdina and Buerstmayr (2004), in which hulless varieties showed lower DON content than hulled lines. However, Chen et al (1991) found the opposite trend in a collection of 4163 Chinese barley varieties, and Legge et al (2004) also noticed the existence of Canadian hulless barley lines with very high DON content.…”
Section: Resultssupporting
confidence: 90%
“…Regarding the correlation of FHB parameters with the hull trait, the results were not consistent in literature. According to Clear et al (1997), over 50% of DON initially present on barley grain could be removed during the dehulling process, which was in agreement with the results of Zhou et al (1991) and Legzdina and Buerstmayr (2004), in which hulless varieties showed lower DON content than hulled lines. However, Chen et al (1991) found the opposite trend in a collection of 4163 Chinese barley varieties, and Legge et al (2004) also noticed the existence of Canadian hulless barley lines with very high DON content.…”
Section: Resultssupporting
confidence: 90%
“…De-hulling of oats led to a T-2/ HT-2 reduction of 98% in the mean, where reduction varied between 93.8% and 100%. These results are similar to those in oats from northern Europe (Scudamore et al 2007) and Canada (Clear et al 1997). The major reduction of T-2/HT-2 toxins obtained by de-hulling clarify why consumer products from retail markets in Germany had very little Table 4.…”
Section: Resultssupporting
confidence: 89%
“…Snijiders et al and Doohan et al reported the ability of the toxin to translocate from chaff to the grain [ 36 , 37 ]. Data from previous studies suggest that the highest accumulation of mycotoxins in the barley hull [ 38 ]. Legzdina et al reported that hulless barley tends to be less prone to mycotoxin contamination than covered barley, assuming a similar level of field FHB severity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%